Syntenin: Key player in cancer exosome biogenesis and uptake?. Issue 2 (4th March 2017) - Fares, Joanna; Kashyap, Rudra; Zimmermann, Pascale
Abstract: Cancer exosomes are gaining considerable amount of attention in basic and applied clinical research for their established role in the modulation of the tumor niche, and their broad-range contribution to tumor-host cross-talk. Supporting evidence to their role in tumorigenesis comes from the observation that exosome secretion, composition and functional effects are all altered as tumors become more aggressive. At the molecular level, the mechanisms underlying exosome biogenesis and uptake are far from being understood. Recent work has highlighted the critical role for the small intracellular adaptor protein syntenin in the biogenesis of a subset of exosomes and loading of cargo. Here, we review this recent work and some unpublished data that further highlight the possible implications of syntenin and the syndecan (SDC) heparan sulphate proteoglycans during exosome uptake, suggesting a supporting role for this pathway in the entire life cycle of cancer exosomes.